The Role of Perceived Partner Responsiveness in the Relationship between Attachment and Subjective Well-Being of Broken Home Women - Clara Josephine; Monty Prawiratirta Satiadarma; Roswiyani (Department of Guidance and Counseling, FIP, Undiksha, 2023)
Feelings of insecurity due to loss of attachment to parents can cause insecure attachment that persists into adulthood, resulting in depression, anxiety, and low self-esteem, as well as affecting subjective well-being. This study aims to analyze the impact of attachment anxiety and attachment avoidance on cognitive aspects related to the subjective well-being of early adult women whose parents are divorced with perceptions of their partner's responsiveness as a moderator variable. This research is included in the type of correlational research. The population in this study was early adult women. Meanwhile, the research sample was 115 early adult women who experienced their parents' divorce before the age of 18. Data collection was carried out using a questionnaire consisting of three measuring tools, namely Experiences in Close Relationships-Revised (ECR-R), Satisfaction with Life Scale (SWLS), and Perceived Partner Responsiveness Scale (PPRS). The data was then analyzed using correlation analysis and regression test analysis. The research results show that insecure attachment has a significant negative relationship with subjective well-being. Meanwhile, perceptions of a partner's responsiveness have a significantly positive relationship with subjective well-being. However, perceived partner responsiveness cannot act as a moderator between insecure attachment and subjective well-being. The implication of this research is that it can provide the latest information regarding the importance of partner responsiveness in supporting the subjective well-being of women from broken homes.